Rocks and Vegetation Cover Improve Body Condition of Desert Lizards during Both Summer and Winter. (1st July 2022) - Stark, Gavin; Ma, Liang; Zeng, Zhi-Gao; Du, Wei-guo; Levy, Ofir
Abstract: Microhabitats provide ecological and physiological benefits to animals, sheltering them from predation and extreme temperatures and offering an additional supply of water and food. However, most studies have assumed no energetic costs of searching for microhabitats or moving between them, or considered how the availability of microhabitats may affect the energy reserves of animals and how such effects may differ between seasons. To fill these gaps, we studied how the body condition of lizards is affected by microhabitat availability in the extreme environment of the Judean Desert. In particular, we quantified how vegetation and rock cover in the vicinity of these lizards affect their body condition during summer and winter. First, we used aerial imagery to map the vegetation/rock cover at two study sites. Next, we collected 68 adult lizards and examined how their body condition varies across seasons and availability of vegetation and rock cover. In addition, we examined how vegetation and rock cover may differ in their effective distance (i.e., the distance that best explains body condition of lizards). We found that lizards body condition was better if they were collected closer to a higher availability of vegetation or rocks. However, while close proximity (within 10 m) was the best predictor for the positive effect of rocks, a greater distance (up to 90 m) was the best predictor for the effect of the vegetation cover. Moreover, the positive effect of vegetation was 12-fold higher than the effect of rocks. Interestingly, although the lizards' body condition during winter was poorer than during summer, the positive effects of rock and vegetation cover remained constant between the seasons. This similarity of benefits across seasons suggests that shaded microhabitats have important additional ecological roles regardless of climate, and that they may provide thermoregulatory benefits in winter too. We also found a synergic effect of vegetation and rock cover on the lizards' body condition, suggesting that their roles are complementary rather than overlapping. Our research has revealed the importance of shade- and shelter-providing microhabitats in both summer and winter. We suggest that proximity to microhabitat diversity may contribute to better body condition in lizards or, alternatively, facilitates competition and attracts lizards with better body condition. Comprehending the complex interactions between animals and different microhabitats is critical for developing better conservation plans, understanding the risks of climate change, and suggesting mitigation strategies.